2013
DOI: 10.1371/journal.pone.0058470
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ASPP2 Interaction with p53 Core Domain by an Intramolecular Autoinhibitory Mechanism

Abstract: ASPP2 is a key protein in regulating apoptosis both in p53-dependent and-independent pathways. The C-terminal part of ASPP2 contains four ankyrin repeats and an SH3 domain (Ank-SH3) that mediate the interactions of ASPP2 with apoptosis related proteins such as p53, Bcl-2 and the p65 subunit of NFκB. p53 core domain (p53CD) binds the n-src loop and the RT loop of ASPP2 SH3. ASPP2 contains a disordered proline rich domain (ASPP2 Pro) that forms an intramolecular autoinhibitory interaction with the Ank-SH3 domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Thus, we could hypothesize that ΔN-ASPP2 also binds p53 to prevent it from occupying p53 target gene promoters or to compete with ASPP2 for p53 binding [4]. Thus ΔN-ASPP2 may also directly bind ASPP2 to inhibit its function as would be predicted by structural studies [34,35]. Intriguingly, we observed that expression of ΔN-ASPP2 appears to suppress expression of ASPP2 (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, we could hypothesize that ΔN-ASPP2 also binds p53 to prevent it from occupying p53 target gene promoters or to compete with ASPP2 for p53 binding [4]. Thus ΔN-ASPP2 may also directly bind ASPP2 to inhibit its function as would be predicted by structural studies [34,35]. Intriguingly, we observed that expression of ΔN-ASPP2 appears to suppress expression of ASPP2 (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Although most of the ASPP2-binding proteins that are critical for its proapoptotic function (p53, NF-κB, Bcl-2) interact with the ankyrin-SH3 domain of ASPP2, the plasma membrane localization and the prosenescence activity of ASPP2 depend on cellular partners that bind ASPP2 at its N-terminal region (41)(42)(43)(44). It was shown (41,45) that peptides generated from the proline-rich domain (e.g., 693-746) could bind to the ankyrin-SH3 domain of ASPP2 and compete for binding with NF-κB or p53. This result raised the possibility that an autoinhibitory intramolecular mechanism exists to regulate associations with ankyrin-SH3 domain.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Disordered regions are particularly subjecttopost-translational modifications, [23][24][25] and many contain sites for phosphorylation. [26,27] HIV-1 Rev is as mall, 116-residue protein, whiche nables packing of the HIV RNA into the emerging virions. [26,27] HIV-1 Rev is as mall, 116-residue protein, whiche nables packing of the HIV RNA into the emerging virions.…”
mentioning
confidence: 99%